Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Let's begin by listing out the given information:
[tex]\begin{gathered} 36x^2+36y^2-36x+48y=-16 \\ \text{dividing through by 36 to remove the coefficients of }x^2,y^2\text{, we have:} \\ \frac{36}{36}x^2-\frac{36}{36}x+\frac{36}{36}y^2+\frac{48}{36}y=-\frac{16}{36} \\ x^2-x+y^2+\frac{4}{3}y=-\frac{4}{9} \\ x^2-x+y^2+\frac{4}{3}y+\frac{4}{9}=0 \\ Comparing\text{ }this\text{ }with\text{ }the\text{ }general\text{ }equation\text{ of }circle\text{ }we\text{ have:} \\ x^2+y^2+2gx+2fy+c=0 \\ \Rightarrow2g=-1 \\ g=-\frac{1}{2} \\ 2f=\frac{2}{3} \\ \Rightarrow f=\frac{1}{3} \\ c=\frac{4}{9} \\ \Rightarrow c=\frac{4}{9} \end{gathered}[/tex]Thus the center of the circle is:
[tex]\begin{gathered} (h,k)=(-g,-f) \\ \Rightarrow(--\frac{1}{2},-\frac{1}{3}) \\ \Rightarrow(\frac{1}{2},-\frac{1}{3}) \\ \\ r=\sqrt{g^{2}+f^{2}-c} \\ r=\sqrt[]{(\frac{1}{2})^2+(-\frac{1}{3})^2-\frac{4}{9}} \\ r=\sqrt[]{\frac{1}{4}+\frac{1}{9}-\frac{4}{9}}=\sqrt[]{-\frac{1}{12}} \\ r=\sqrt[]{-\frac{1}{12}} \end{gathered}[/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.